2006
DOI: 10.1021/jp064811m
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of Alkanes in the Gas Phase and Pure Liquids

Abstract: Monte Carlo (MC) statistical mechanics simulations have been carried out for the homologous alkane series of n-butane through n-dodecane in the gas phase and for the pure liquids at 298 K and 1 atm using the OPLS-AA force field. The study addresses potential cumulative deviations of computed properties and potential conformational differences between the gas phase and pure liquids, for example, from self-solvation in the gas phase. The average errors in comparison with experimental data for the computed densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
141
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(163 citation statements)
references
References 28 publications
(63 reference statements)
18
141
0
3
Order By: Relevance
“…The results are in good agreement to previous reports on pure hydrocarbons (modeled using United-Atom or All-Atom force fields) (Feng et al 2013;Ferguson et al 2009;Thomas et al 2006). Comparison against the bulk-configuration results shows reduction in these properties, which is more conspicuous for longer chain hydrocarbons.…”
Section: Radius Of Gyration and End-to-end Distancesupporting
confidence: 90%
“…The results are in good agreement to previous reports on pure hydrocarbons (modeled using United-Atom or All-Atom force fields) (Feng et al 2013;Ferguson et al 2009;Thomas et al 2006). Comparison against the bulk-configuration results shows reduction in these properties, which is more conspicuous for longer chain hydrocarbons.…”
Section: Radius Of Gyration and End-to-end Distancesupporting
confidence: 90%
“…Lee used the heat of vaporization to calculate E a for liquid alkanes and he used the Monte Carlo simulations of Jorgensen, et al (21,22) to find E a for the aqueous solutions. The simulation results for liquid hydrocarbons were tested against experiment (21,23) by calculating the heats of vaporization and densities of the liquid hydrocarbons; the estimated and experimental values agreed within 2% for alkanes with six or fewer carbon atoms (23). Lee's goal (14) in 1991 was to test how well scaled particle theory calculates the cavity work, as his 1985 model for the hydrophobicity of water [based on the small size of the water molecule (13)] relied on calculations made with scaled particle theory, as did much of the earlier work on the hydrophobicity of water (24,25).…”
Section: Resultsmentioning
confidence: 99%
“…For linear alkanes experimental gauche-trans energy differences were reported ranging from approximately 0.5 to 1.0 kcal mol −1 (21-23) in the gas phase and are in the range of 0.5-0.6 kcal mol −1 in the liquid (22). An electron diffraction study of the alkanes butane through heptane revealed that the gas-phase conformations often contain gauche dihedral angles (24), and earlier molecular dynamics studies predicted that gauche population should be enhanced upon transfer from the gas phase to the liquid (25) Fig.…”
Section: Resultsmentioning
confidence: 99%